Retail Green Sukuk in Indonesia: Toward A Maqashid Approach - Khalilurrahman Khalilurrahman; Husni Mubarrak (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
Recent global trends include an increase in demand for sustainable development goals (SDGs) and green sukuk programs. The initiative has gained prominence due to the severe effects of climate change, global warming, and other environmental issues. With its green bond and green sukuk framework, Indonesia has endeavored to mitigate this effect. In response, the Indonesian government has issued Sukuk Tabungan (ST), which is designed to finance green projects. This article will examine the structure and performance of the Sukuk al-Wakalah contract, as well as the Maqashid method used to determine the mashlahah and priority level of Sukuk Tabungan, using the library research method and descriptive analysis. The study's findings indicate that Sukuk Tabungan could contribute to the achievement of the Sustainable Development Goals (SDGs) because it is designed in accordance with maqashid, which avoids Sharia-compliant practices in order to perform mashlahah. Even though it has a lower coupon rate and is of a smaller size than Sukuk Ritel, it has a high likelihood of being issued because its proceeds will be used exclusively to finance green projects in order to accelerate the Sustainable Development Goals. In addition, the objective of sukuk al Wakalah issuance appears to fall within the imperative level or dharuriyat of the Maqashid framework due to its five targeted projects, in accordance with the Islamic legal maxims "harm is to be eliminated" and "avoidance of harm takes precedence over the attainment of benefit," which should be the primary reason for the issuance of this Sukuk.========================================================================================================================================ABSTRAK – Sukuk Hijau Ritel di Indonesia: Sebuah Tinjauan Maqashid. Kebutuhan akan keberlangsungan tujuan pembangunan berkelanjutan (SDGs) dan sukuk hijau kian menjadi tren dunia belakangan ini. Inisiasi tersebut muncul ke permukaan sebagai respon terhadap dampak buruk perubahan iklim, pemanasan global dan isu lingkungan lainnya. Indonesia dengan kerangka program obligasi dan sukuk hijau (green bond dan green sukuk) mencoba mengatasi dampak buruk akibat isu tersebut. Sebagai tindak lanjut, Pemerintah Indonesia meluncurkan green sukuk, atau Sukuk Tabungan (ST) yang ditujukan untuk membiayai proyek hijau (green project). Dengan menggunakan studi literatur kepustakaan sebagai metode secara deskriptif analisis, artikel ini berupaya mendiskusikan lebih jauh struktur dan performa dari sukuk al wakalah, serta pendekatan Maqashid yang digunakan untuk menentukan kemaslahatan dan tingkat prioritas dari pembiayaan Sukuk Tabungan. Temuan penelitian menyimpulkan bahwa, Sukuk Tabungan harus menghindari dari praktik yang tidak sesuai dengan prinsip Syariah. Meskipun memiliki kupon yang lebih kecil dan jumlah yang lebih sedikit dari Sukuk Ritel, Sukuk Tabungan punya potensi yang besar untuk dikembangkan karena dana sukuk tersebut ditujukan secara khusus untuk membiayai proyek hijau demi mempercepat SDGs. Tujuan peluncuran sukuk al wakalah dapat disimpulkan terdapat pada level yang sangat penting atau dharuriyat, berdasarkan kerangka Maqashid, dikarenakan tujuan pembiayaannya pada lima target area, sejalan dengan kaedah fiqh yaitu “kemudaratan harus dihilangkan” dan “mencegah kemudaratan lebih utama ketimbang mencapai kemaslahatan”.